Multicultural Competencies: A 30-Year Content Analysis of American Counseling Association Journals - Vanessa Placeres; Don Davis; Sarah Gazaway; Nic Williams; Erin Mason; Wendy Hsu; Lina Alsaegh; Tania Quintero Rico; Brittany Glover (Teaching and Supervision in Counseling, 2024)
We conducted a 30-year content analysis (1987-2017) on quantitative literature about multicultural counseling competencies in American Counseling Association journals. Fifty-five articles were coded for leading contributors, specialty, intrapersonal counselor characteristics, training/education curriculum, study design, multicultural perception, and counseling outcomes. We discuss gaps in the literature and make recommendations for counselor education, teaching, and future research.
Keywords: multicultural counseling competencies; American Counseling Association journals; content analysis